Infection with Toxoplasma gondii (Eucoccidiorida: Sarcocystidae) in bats of Campeche and Yucatán, Mexico - Torres-Castro, Marco (2019)
Toxoplasma gondii is a protozoan parasite recognized as the causative agent of toxoplasmosis, a zoonotic disease that affects humans and domestic or wild animals. In Mexico, it represents a public and animal health problem, especially in regions with tropical and subtropical climates. Bats have been reported as accidental hosts in the transmission cycle; however, there is no preceding information in Mexico. Therefore, the aim of the present study is to report the T. gondii infection in bats captured in sites of Campeche and Yucatan states, Mexico. Bats were captured in two sites in Yucatan (X’matkuil and Panaba) and one in Campeche (Hampolol), located in the Yucatan Peninsula. Kidneys, spleen, and liver were collected and used in the total DNA extraction. Toxoplasma gondii infection was detected through the amplification of a B1 gene fragment, using nested PCR. The positive PCR products were purified and sent to sequencing for a posterior sequence identity analysis. Additionally, a phylogenetic tree was made. A total of 69 bats belonging to eight different species were processed: 41 (59.4 %, 41/69) Artibeus jamaicensis; six (8.7 %, 6/69) Pteronotus parnellii; six (8.7 %, 6/69) Noctilio leporinus; six (8.7 %, 6/69) Chiroderma villosum; four (5.8 %, 4/69) Glossophaga soricina; two (2.9 %, 2/69) Carollia sowelli; two (2.89 %, 2/69) Artibeus lituratus; and two (2.9 %, 2/69) Rhogeessa aeneus. The nested PCR identified eight (11.6 %, 8/69) infected bats: six (75 %, 6/8) A. jamaicensis, captured in X'matkuil and Panaba, one (12.5 %, 1/8) G. soricina, and one (12.5 %, 1/8) C. villosum, both captured in Panaba. The alignment analysis yielded 99-100 % for cover and 97-99 % for identity to T. gondii sequences. Our results contribute to the understanding of the T. gondii transmission cycle in the region; however, future research is needed to determine circulating genotypes, as previous studies have demonstrated that these animals might be infected with identified genotypes in other domestic or wild animals and even in humans.